2019
DOI: 10.1021/acs.inorgchem.9b00853
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Stability, and Inhibition of Tubulin Polymerization by RuIIp-Cymene Complexes of Trimethoxyaniline-Based Schiff Bases

Abstract: Four trimethoxy-and dimethoxyphenylamine-based Schiff base (L1−L4)-bearing Ru II −p-cymene complexes (1−4) of the chemical formula [Ru II (η 6 -p-cymene)(L)(Cl)] were synthesized, isolated in pure form, and structurally characterized using single-crystal X-ray diffraction and other analytical techniques. The complexes showed excellent in vitro antiproliferative activity against *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
4
25
0
Order By: Relevance
“…The above result corroborated with the instantaneously monoaquated complex formed using 1.1 equivalents of AgNO 3 in a 3 : 7 (v/v) DMSO-d 6 : D 2 O mixture (Figure 4, S41, S42, S43). Similar features were observed earlier for other N,O coordinated Ru II (p-cymene) complexes [67,72] suggesting that perhaps the resultant monocationic Ru II is a preferred state in aqueous solution at pH 7.4. After hydrolysis, the monoaquated complexes of 7-9, remain stable for ca.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The above result corroborated with the instantaneously monoaquated complex formed using 1.1 equivalents of AgNO 3 in a 3 : 7 (v/v) DMSO-d 6 : D 2 O mixture (Figure 4, S41, S42, S43). Similar features were observed earlier for other N,O coordinated Ru II (p-cymene) complexes [67,72] suggesting that perhaps the resultant monocationic Ru II is a preferred state in aqueous solution at pH 7.4. After hydrolysis, the monoaquated complexes of 7-9, remain stable for ca.…”
Section: Resultssupporting
confidence: 86%
“…[57] It has been found that p-cymene based Ru II complexes may be an effective choice against triple-negative breast cancer cells. [58][59][60][61][62][63][64] In our endeavors, we have generated cytotoxic Ru II -(pcymene) complexes of imidazole, benzimidazole, anthraimidazoledione and aryl trimethoxy based ligand systems, with excellent efficacy against TNBC, [53,55,[65][66][67] pancreatic cancer, [54] and colon cancer. [65] To gain further insight if the N,N vs. N,O coordination proceeds with differences in stability and cell killing pathways, we designed nine Ru II (p-cymene) complexes of 3-aminobenzoate while varying the aldehydes (pyridine-2carboxaldehyde, imidazole-2-carboxaldehyde, salicylaldehyde, 2-hydroxynaphthaldehyde and ortho-vanillin) generating ligands L1-L7.…”
Section: Introductionmentioning
confidence: 99%
“…Some have shown a promising characterization as an immune-modulating anticancer agent, 145 excellent redox potential, 97 strong topoisomerase inhibitor, 98 while others have shown encouraging results such as antimetastatic activity, tubulin formation inhibition, and high selectivity against cancer cells over normal cells. [146][147][148] Recent investigations cover structurally novel scaffolds including electron-deficient ruthenium complexes 149 and macromolecular ligands such as dendrimers. 150 In this review, we present a brief description of Ru-based anticancer complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The complexes that demonstrated a lower toxicity were selected to test their effect on the inhibition of the microtubule network in the MDA-MB-231 cell line. In silico and in vitro studies demonstrated good binding between the compounds and the tubulin, as well as antiproliferative action against advanced subtypes of cancer, such as triple-negative metastatic BC [50].…”
Section: New Synthesized Moleculesmentioning
confidence: 97%
“…Ruarene complexes have been observed to be possible agents against cisplatin resistance with fewer side effects, demonstrating a different mechanism of action. Acharya et al synthesized four ruarene complexes and characterized them using X-ray crystallography [50], and molecular docking was performed to demonstrate their ability to bind tubulin proteins (PDB: 1SA0). The cytotoxicity of the molecules was tested in vitro by MTT assays in three different cancer cell lines, including MDA-MB-231.…”
Section: New Synthesized Moleculesmentioning
confidence: 99%